FACTORS OF AGGRESSIVE BEHAVIOR AMONG MOTORCYCLE DRIVERS AND ITS RELATIONSHIP WITH DANGEROUS DRIVING INDEX IN THE STATE OF PENANG - Mageswaran Senderal; Saralah Devi Mariamdaran Chethiyar; Muzlifah Binti Azmi (Polteknik Ilmu Pemasyarakatan, 2021)
This study aims to identify the factors of aggressive behavior among motorcyclists in the state of Penang. Also identify the relationship between aggressive behavior factors and the dangerous driving index. This study is quantitative in nature by distributing questionnaires to 140 individuals who have been convicted under Section 42 (1) of the Road Transport Act 1987. Descriptive and inferential analysis methods are used to answer the research questions. Independent sample t-tests and one-way Anova were conducted to identify differences in the level of aggressive behavior among respondents based on demographic factors and conducted Pearson correlation analysis to identify the relationship between the two study variables. The findings of this study provide real figures related to the level of aggressive behavior from the perception of individuals who have ever made such mistakes. Independent sample t tests showed that there were behavioral differences based on gender factors. Meanwhile, one-way Anova test shows that there are differences based on employment factors and not education level. Correlation analysis showed that there was a relationship between aggressive behavior with a dangerous driving index with a value of r 0.349. Thus, this study helps in identifying the relationship between aggressive behavior and against the increase in the dangerous driving index among motorcyclists. All parties should mobilize their energy to reduce the dangerous driving index and pose a danger due to aggressive behavior factors on the road.